Ecological Crisis in Popular Culture Construction Natural Representation in BONG JOON-HO’S FILM “OKJA” - Putri, Karimah Kinanti; Harahap, Rahma Hayati (Talenta Publisher, 2025)
The ecological crisis has become one of the most pressing global issues, triggered by the uncontrolled exploitation of nature due to capitalism and industrialization. This research aims to analyze the representation of the ecological crisis in popular culture through the film Okja (2017) by Bong Joon-ho. This film depicts the relationship between humans, nature, and animals in the context of modern capitalism, which often uses nature as a commodity for economic gain. Using a conflict theory approach in ecological sociology, this research highlights how capitalism damages ecosystems and exacerbates social injustice. In the film Okja, nature and animals are depicted as victims of exploitation by a capitalist system that does not care about ecological welfare. The conflict between economic interests and nature conservation in this film reflects the reality modern society faces. This research uses a content analysis method to explore how the film conveys ecological messages relevant to real conditions. The research results show that popular culture, especially films, has great potential in increasing public awareness of environmental issues. Okja not only offers criticism of capitalism and the exploitation of nature but also acts as an advocacy medium capable of inspiring social change in the way society views and treats the environment. Thus, this film becomes an important tool in communicating the ecological crisis and challenging society to care more about nature conservation.